Pendampingan Pastoral Keluarga Dalam Mengukuhkan Hakikat Sakramen Perkawinan Menurut Iman Katolik - Benedikta Boleng (Jayapangus Press, 2021)
This research was conducted to determine the extent to which Catholic families in the Diocese of Ende received family assistance from the Church (Parish); (2) Finding mentoring strategies that can be used in family pastoral mentoring activities; (3) Through proper accompaniment activities, Catholic families can be brought to a clear understanding and appreciation of the noble meaning of their marriage. The number of respondents was 140 people, data was obtained through a questionnaire distributed to Catholic families who had received the Sacrament of Marriage. The data analysis technique in this study used Chi-Square analysis. The results showed that family pastoral assistance reached a quality scale of 75.86% or was in the effective category, while the embodiment of the values ​​of the Sacrament of Marriage reached 78.71% which means good. The mean of variables I and II using the Chi Square count shows the result of 12.06 which is greater (>) than the Chi Square table 7.82 which means significant. This means that the family pastoral assistance that has been carried out has a significant relationship with the understanding and appreciation of the people of the noble meaning of their marriage.